2004
DOI: 10.1002/prot.20321
|View full text |Cite
|
Sign up to set email alerts
|

Predicting protein functional sites with phylogenetic motifs

Abstract: In this report, we demonstrate that phylogenetic motifs, sequence regions conserving the overall familial phylogeny, represent a promising approach to protein functional site prediction. Across our structurally and functionally heterogeneous data set, phylogenetic motifs consistently correspond to functional sites defined by both surface loops and active site clefts. Additionally, the partially buried prosthetic group regions of cytochrome P450 and succinate dehydrogenase are identified as phylogenetic motifs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
68
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 48 publications
3
68
0
Order By: Relevance
“…A variety of approaches are being applied that include aligning structures to match a few consensus or enzymatic catalytic residues, [14][15][16][17][18][19][20][21][22][23] identifi cation of cavities consistent with shapes of known ligands, 24 a sequence independent force fi eld to extract common active site features, 25 theoretical prediction of titration curves, 26 using chemical properties and electrostatic potentials of amino acid residues consistent with active site characteristics, 27,28 neural network analysis of spatial clustering of residues, 29 and conserved residues from multiple sequence alignments (phylogenetic motifs). 20,30 Nevertheless, direct experimental observation of protein-ligand interactions are a more reliable mechanism for the proper and accurate identifi cation of protein active sites. LigBase is an online database that aligns only active sites present in the protein data bank (PDB) that bind the identical ligand, using structure and sequence alignments.…”
mentioning
confidence: 99%
“…A variety of approaches are being applied that include aligning structures to match a few consensus or enzymatic catalytic residues, [14][15][16][17][18][19][20][21][22][23] identifi cation of cavities consistent with shapes of known ligands, 24 a sequence independent force fi eld to extract common active site features, 25 theoretical prediction of titration curves, 26 using chemical properties and electrostatic potentials of amino acid residues consistent with active site characteristics, 27,28 neural network analysis of spatial clustering of residues, 29 and conserved residues from multiple sequence alignments (phylogenetic motifs). 20,30 Nevertheless, direct experimental observation of protein-ligand interactions are a more reliable mechanism for the proper and accurate identifi cation of protein active sites. LigBase is an online database that aligns only active sites present in the protein data bank (PDB) that bind the identical ligand, using structure and sequence alignments.…”
mentioning
confidence: 99%
“…Recently, we demonstrated that sequence fragments conserving the overall phylogeny, termed phylogenetic motifs (PMs), are very likely to correspond to protein functional sites [12]. We briefly highlight the key results of our previous report here (see Implementation for a technical description of the approach).…”
Section: Introductionmentioning
confidence: 93%
“…Derivatives of the ET method have been recently proposed demonstrating that motifs taken from regions known to be functionally important a priori conserve the overall phylogeny of the family [256]. These Phylogenetic Motifs (PM) frequently correspond to key protein functional sites and recently a web based application has been developed [257]. Due to its nature, ET analysis is limited by the availability of a sufficiently large and diverse set of related proteins.…”
Section: Functional Descriptors From Structurementioning
confidence: 99%